Distribution of Monocarboxylate Transporters in Brain and Choroid Plexus Epithelium - Masaki Ueno; Yoichi Chiba; Ryuta Murakami; Yumi Miyai; Koichi Matsumoto; Keiji Wakamatsu; Genta Takebayashi; Naoya Uemura; Ken Yanase (MDPI AG, 2023)
The choroid plexus (CP) plays central roles in regulating the microenvironment of the central nervous system by secreting the majority of cerebrospinal fluid (CSF) and controlling its composition. A monolayer of epithelial cells of CP plays a significant role in forming the blood-CSF barrier to restrict the movement of substances between the blood and ventricles. CP epithelial cells are equipped with transporters for glucose and lactate that are used as energy sources. There are many review papers on glucose transporters in CP epithelial cells. On the other hand, distribution of monocarboxylate transporters (MCTs) in CP epithelial cells has received less attention compared with glucose transporters. Some MCTs are known to transport lactate, pyruvate, and ketone bodies, whereas others transport thyroid hormones. Since CP epithelial cells have significant carrier functions as well as the barrier function, a decline in the expression and function of these transporters leads to a poor supply of thyroid hormones as well as lactate and can contribute to the process of age-associated brain impairment and pathophysiology of neurodegenerative diseases. In this review paper, recent findings regarding the distribution and significance of MCTs in the brain, especially in CP epithelial cells, are summarized.